SP0103 Chronic renal failure in systemic rheumatic diseases. (1st June 2001) - Tesar, V
Abstract : Prevalence of end-stage chronic renal failure (ESRF) in patients with systemic lupus erythematosus (SLE) and lupus nephritis varies considerably, supposedly due to not completely comparable groups of patients and different modes of treatment, but it may be estimated that about 15–20% of patients with lupus nephritis ultimately reach ESRF. This proportion is probably similar in adults and children, but may be substantially higher in African Americans (43% in one study). Rapid progression to ESRF during the first year of follow-up is uncommon and may occur in some patients with active multisystem disease, more than half of patients with lupus nephritis ultimately reaching ESRF do so in more than 5 years. Chronic renal failure may be reversible in about 20% of patients with lupus nephritis starting dialysis treatment. Although the mechanisms of this very high reversibility of renal failure in lupus nephritis remain unclear, immunosuppressive treatment does not seem to be of utmost importance and other factors (e.g. hypertension, renal vasoconstriction, endothelial dysfunction, etc.) may play a role. The view that the activity of SLE remits when lupus nephritis progresses to ESRF (so called lupus burn-out) is probably no longer substantiated and according to the Dutch study 71% of patients with lupus nephritis progressing to ESRF had flares with multisystem involvement in the last 4 years before the initiation of dialysis treatment. Lupus nephritis may represent between 1–4% of all patients treated by renal replacement therapy, their mean age is about 30 and males are more represented than in unselected SLE population. Estimated 5-year survival during hemodialysis treatment is between 81–89% and is at least comparable to other dialysis patients. Rather surprisingly, 5- and 10-year survival of patients with lupus nephritis treated by renal replacement therapy is not different from the survival of patients not progressing to ESRF. Extrarenal activity of SLE seems to be lower in patients treated by hemodialysis, but some extrarenal activity may be present in bout 2/3 of dialyzed patients. Vascular access thrombosis may be much more frequent in dialyzed patients with lupus nephritis compared to other causes of ESRF, the role of antiphospholipid antibodies is suspected, but not firmly substantiated. Experience with peritoneal dialysis in patients with lupus nephritis is limited and the potential risk of infectious complications is of major concern. Renal transplantation results in relatively high risk of not surviving in the first year after transplantation (5–15% mainly due to infectious complications. 5-year cadaveric graft survival is about 60% and renal transplantation probably does not result in higher 5-year survival than hemodialysis. Recurrence of lupus nephritis in transplants is rare, milder and better controlled by the instituted therapy. Repeated requirement of longer dialysis treatment (usually 6–12 months) before transplantation to achieve disease quiescence does not seem to be fully substantiated. Acute renal failure is a common presentation of ANCA-positive renal vasculitis with focal segmental necrotizing/crescentic glomerulonephritis. Dialysis dependent renal failure may occur in 24–63% of these patients (of mean age 50–60 years) according to the severity of disease and time of referral. Early immunosuppressive treatment is able to spare renal function, e.g. initial dialysis was required in 59% and long-term dialysis in only 36% of patients from Wessex. Need for dialysis clearly confers poorer 5-year survival (about 50% vs. 75%). Renal transplantion is probably performed in no more than 10% of (usually younger patients with 92% 1-year patient and 85% 1-year graft survival. Delay in diagnosis and treatment remains to limit the therapeutic potential of current immunosuppressive treatment to improve lon-term outcome of these patients. References: Nossent JC, Swaak AJG, Berden JHM. Systemic lupus erythematosus: analysis of disease activity in 55 patients with end-stage renal failure treated with hemodialysis or continuous ambulatory peritoneal dialysis. Am J Med. 1990;89:169–74 Hedger N, Stevens J, Drey N, et al . Incidence and outcome of pauci-immune rapidly progressive glomerulonephritis in Wessex, UK: a 10-year retrospective study. Nephrol Dial Transplant. 2000;15:1593–9